(3QSGdI GddeYI GdCdeYjI aj HjGf eYfi GdeYjIs - (3CHh GdWjH EHQGgje Hf eMehO GdGbUQGFj GdTGPdj GdehGgHjs ((3eMehO UObi s)
(3ChdgG (B:s
(3HSe Gddg GdMQef GdQMje GdMeO ddg GdefaQO HUaGJ GdceGd hHYO agPg deYI SfjI ai HjGf eYfi GdeYjI GdhGQOI ai GdfUhU GdbQBfjI hGdCMGOjK GdfHhjI GdKGHJI HPdc s
(3BNQgG (B:s
(3hgcPG EfeG cGfJ ai YhGde HSGWJgG hJQcjHgG hEVGaJgG hJLQjOgG ef CRd GdCRGd hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds